An Elaboration Of Broiler Chicken Productivity In Open And Closed House Systems: A Case Study At Abdul Aziz Jaba Farm, Luyo Sub-District - Sulfawati , Sulfawati; Asrandi , Asrandi; Suhab, Resky Faradibah (Jurnal Economic Resource, 2025)
Broiler chickens are a vital poultry commodity that plays a significant role in meeting the protein needs of the Indonesian population. The increasing demand for chicken meat has encouraged poultry farmers to improve efficiency and productivity. One strategy to achieve this is by selecting the appropriate housing system. This study aims to compare the productivity of broiler chickens raised in two different housing systems open house and closed house under different scales of partnership-based poultry businesses in Dusun Pepalang, Luyo District. The key indicators analyzed include body weight gain, feed conversion ratio (FCR), mortality rate, and performance index (IP). The research uses a descriptive quantitative method with a direct observation approach. Primary data were collected through interviews and field observations, while secondary data were obtained from literature and related documents. The results show that the closed house system offers better productivity and feed efficiency, with lower mortality rates and more uniform growth than the open house system. However, the closed house system requires higher capital investment. These findings can serve as a valuable reference for poultry farmers in choosing the most suitable housing system based on business scale and production goals.